COMPARATIVE ANALYSIS OF THE GENERAL PHYSICAL FITNESS OF QUALIFIED POLYATHLONISTS - Martirosova, T.A.; Kondrashova, E.D.; Gorbachev, A.S.; Maleev, P.A. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to identify differences in the indicators of physical fitness of polyathletes of the 1st sports category and masters of sports and to evaluate their impact on sports results. Methods and structure of the study. More than 20 young men and juniors with the 1st sports category and 15 men who are active masters of sports in polyathlon took part in the scientific work. The research methods in this scientific work were the analysis of scientific and methodological literature, pedagogical testing, as well as mathematical and statistical data processing. As control tests, tests were selected that are most often covered in scientific research literature and used in the theory and practice of physical education and sports to determine the level of general physical fitness of athletes. Results and conclusions. The analysis made it possible to establish the level of general physical fitness of qualified Krasnoyarsk polyathletes. In this scientific work, the reliability of differences between the studied parameters of polyathletes with the I sports category and polyathletes with the sports title of master of sports was evaluated, and a correlation analysis was carried out in order to identify the influence of the studied indicators on the sports results of athletes. The study allows us to correct the basis of scientifically based model characteristics for the further growth of the sports qualification of polyathletes in the Krasnoyarsk Territory, as well as to determine the main factors for the effective management of the training process of athletes of different age categories.